PAI Learning Model Based on Mandar Local Wisdom in Cultivating Religious Character in Students at MA BPII Pamboang - Husnul Khatimah; Siri Dangnga; Abd. Halik; Usman Noer; Musyarif (Universitas Muhammadiyah Palu, 2024)
The aim of this research is to find out how the approaches, strategies, learning methods, techniques and tactics for learning Islamic religious education based on Mandar local wisdom in cultivating the religious character of students at MA BPII Pamboang. The type of research used is qualitative research and the research instruments used are observation, interviews and documentation. The data analysis technique uses data reduction, data presentation and conclusion drawing. The results of this research show that: the PAI learning approach based on Mandar local wisdom in cultivating religious character at MA BPII Pamboang can be done by applying a problem-based learning model approach so that students can have an attitude; (1) Malappuq. (2) Pangayaq, (3) Sipakatau, (4) Manarang/ pore akkalanna. PAI Learning Strategies Based on Mandar Local Wisdom for the Formation of Religious Character of Students at MA BPII Pamboang include integration of local wisdom values, introduction to Mandar religious history and traditions, Experience Based Learning, local religious stories and tales, and behavioral models. Islamic religious education learning methods based on Mandar local wisdom in cultivating the religious character of students at MA BPII Pamboang. In this learning method, the class XI PAI (moral beliefs) teacher applies a lecture and discussion learning model to achieve the goal. The lecture learning method is an approach where a teacher actively conveys information and material to students in the form of oral presentations. Mandar local wisdom-based Islamic religious education learning techniques in cultivating the religious character of students at MA BPII Pamboang; (1) Explore local wisdom values. (2) Tolerance and openness, where local wisdom teaches the values of tolerance and openness to differences in religion, culture and views of life, (3) Togetherness and solidarity, (4) Case studies from local wisdom, (5) Application of values religious values and self-evaluation. Islamic religious education learning tactics based on Mandar local wisdom in cultivating the religious character of students at MA BPII Pamboang; (1) Simulations and role plays, (2) Group discussions, (3) Presentations and learning, (4) Use of local languages in learning.